Improved immunogenicity and protection against enterotoxaemia in sheep by saponin and aluminium hydroxide gel co-adjuvanted vaccine - C, SUNITA S; CHATURVEDI, V K; GUPTA, P K; SUMITHRA, T G; RAI, A K; BINCY, J; GAURI, A C (The Indian Journal of Animal Sciences, 2013)
Immuno-prophylaxis is the most effective control measure for enterotoxaemia, a devastating disease of small ruminants caused by Clostridium perfringens type D. Realizing the problems associated with short term immunity of current enterotoxaemia vaccines, a new formulation using saponin and aluminium hydroxide gel as adjuvants (ASV) was made. Immune response generated in the principal target species, sheep was evaluated in comparison with saponified vaccine (SV) and presently available toxoid vaccine (TV) by indirect ELISA, mice neutralization test (MNT) and standard tube agglutination test (STAT). Out of the 3 vaccines tested, ASV generated the maximum protective immune response with persistent high titers of neutralizing antibodies as denoted by ELISA and STAT. Furthermore, MNT revealed that ASV was able to create protection up to 11 months while it was only for 30 days in TV and SV. This is the first report of a vaccine which offers protection for 11 months against enterotoxaemia in sheep.